2023
DOI: 10.1111/jse.12935
|View full text |Cite
|
Sign up to set email alerts
|

Time to update the sectional classification of Ilex (Aquifoliaceae): New insights from Ilex phylogeny, morphology, and distribution

Abstract: Resolving the infrageneric classification of species‐rich genera has been challenging in plant taxonomy. Ilex L. is a subcosmopolitan genus with over 600 species of dioecious trees and shrubs. Many classification systems based on morphological data have been proposed during the past 250 years. However, these systems (such as Loesener's and Galle's systems) may not truly reflect Ilex's evolutionary trajectories because most of those system's infrageneric hierarchies are not monophyletic. In this study, we recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Photos of leaves, flowers, pollens, whole plants, and so on were collected from our group. The phylogenetic tree was obtained from Yang’s research ( Yang et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photos of leaves, flowers, pollens, whole plants, and so on were collected from our group. The phylogenetic tree was obtained from Yang’s research ( Yang et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue Expression tool interactively displays transcriptomic datasets among distinct developmental stages of fruits and leaves. Phylogenetic Tree enables users to search against the most recent taxonomic relationship of Aquifoliaceae according to Yang’s study ( Yang et al., 2023 ). Literature is used to fast retrieval and access published researches on holly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of phylogeny, DNA molecular evidence has been widely used to reveal evolutionary relationships between species. A series of regional and global studies have been reported [1,[4][5][6][7]23,24]. As for genome studies, currently, only a small number of reports focus on the whole genome [25,26] and mitochondria genome [27].…”
Section: Introductionmentioning
confidence: 99%
“…Morphological intermediacy further divulges clues of hybridizations for its common application in the identi cation of natural hybrids (Marczewski et al 2016). As the development of molecular approaches, there are more available tools to help to unmask hybrids, including but not limited to incomplete ITS (internal transcribed spacer region) concerted evolution (Grimm & Denk 2008 Ilex, the sole genus of Aquifoliaceae, consists of at least 14 sections (Yang et al 2022) and holds more than 600 species as well as a lot of interspeci c hybrids both naturally occurring and cultivated (Galle 1997;Powell et al 2000;Loizeau et al 2005;Chen et al 2008). To date, the con rmed inarti cial Ilex crosses have only been found to be intra-sectional; however, most natural hybrids are concentrated in the largest section, I. sect.…”
Section: Introductionmentioning
confidence: 99%